Study on mechanical and energy properties of rock-like specimens under the effect of loading rate - Jingke Wu; Fuxing Xie (PLoS ONE, 2026)
To investigate the effects of loading rate on the strength evolution, failure mechanism and energy properties of rock-like materials, rock-like specimens were prepared using similar materials, and tests under variable loading rate were conducted through uniaxial compression. Standard cylindrical specimens were fabricated with a fixed sand-binder ratio of 1:9 and three cement-gypsum ratios (1:9, 5:5 and 9:1), using river sand as aggregate and ordinary Portland cement and building gypsum as cementitious materials. The tests were conducted under two loading modes: displacement loading and force loading. The results show that the density of rock-like specimens increases linearly with the rise of cement-gypsum ratio; the stress-strain curves of specimens with different mix ratios all exhibit four stages, namely compaction, elasticity, yield and failure. The uniaxial compressive strength, elastic modulus and deformation modulus increase in the form of logarithmic function with the increase of loading rate, while the peak strain decreases logarithmically; all specimens present columnar splitting failure, and the stress concentration effect induced by force loading is more significant, resulting in a higher degree of failure compared with displacement loading. Moreover, the higher the loading rate, the more fully developed the fractures and the poorer the integrity of specimens. In terms of energy conversion, the lower the loading rate, the smaller the percentage of releasable elastic energy in the absorbed energy (the value of U e / U is greater than 70%), and the larger the percentage of dissipated energy in the absorbed energy (the value of U d / U is less than 30%). As the loading rate increases, U e / U increases as a logarithmic function, while U d / U exhibits an opposite trend. The findings of this study can provide a reference for support design and stability control in deep soft rock engineering.